SIFAT FISIK DAN ORGANOLEPTIK BERAS TIRUAN YANG DIBUAT DENGAN VARIASI LAMA PENGADUKAN DAN WAKTU AGING - Triana Lindriati; . Djumarti; Lusinda Munika Sari (JURNAL AGROTEKNOLOGI, 2013)
Making artificial rice is an important step in the framework of the national food security program. Study is divided into two parts, where Research I was varying the time of stirring and Research II was studying aging time. Stirring and aging should be studied because it affects the pragelatinisation process. The results showed that the time of stirring on artificial rice significantly affect rehydration power, dispersed material, and swelling power. While the aging time effect on the brightness, power rehydration, dispersed material, and swelling power. In organoleptic parameters, stirring has no effect on the value, preverences of color, flavor, aroma, appearance, and overall. While the aging time affects the value appearance and overall. Artificial rice which has the most excellent consumer acceptance is that the long treatment of 20 minutes stirring and 3 days aging time. Artificial rice stirring at 20-minute treatment has a brightness value of 52,8; 141,2% power rehydration; dispersed material 4,1%; and swelling power 244,2%. While artificial rice with 3 days aging treatment has the lightness value of 50,9; power rehydration 78,9%; 13,6% dispersed material; 234,3% swelling power.Keywords: artificial rice, MOCAF, pragelatinisation, consumer acceptance